Matthew Arnold : a literary life (St. Martin's Press, 1998)
"Nearly everyone agrees that Arnold is a central figure in Victorian literature, yet his place in literary history is difficult to define. Tracing Arnold's literary development through his life helps us to understand the peculiar nature of his accomplishments. This book is an attempt to show how his poetry and prose grew out of his personal, social and professional life. Certain interesting features of Arnold's life and literary career have been widely discussed: the problematic influence of his headmaster-father, his intense and uneasy friendship with the poet Arthur Hugh Clough, his relationship with the mysterious 'Marguerite' of the 'Switzerland' poems, his retraction of the important poem Empedocles on Etna in 1853 and his subsequent 'failure' to write introspective poetry. Clinton Machann re-examines these subjects and their place in the evolution of Arnold's writings and casts new light on the forces that shaped the career of this extraordinary man of letters."--BOOK JACKET